Overexpression of the Chromosome Partitioning Gene parA in Azorhizobium caulinodans ORS571 Alters the Bacteroid Morphotype in Sesbania rostrata Stem Nodules - Chien, Hsiao-Lin; Huang, Wan-Zhen; Tsai, Ming-Yen; Cheng, Chiung-Hsiang; Liu, Chi-Te (Frontiers in Microbiology, 2019)
Azorhizobium caulinodans ORS571 is a diazotroph that forms N2-fixing nodules on the roots and stems of the tropical legume Sesbania rostrata. Deletion of the parA gene of this bacterium results in cell cycle defects, pleiomorphic cell shape, and formation of immature stem nodules on its host plant. In this study, we constructed a parA overexpression mutant (PnptII-parA) to complement a previous study and provide new insights into bacteroid formation. We found that overproduction of ParA did not affect growth, cell morphology, chromosome partitioning, or vegetative nitrogen fixation in the free-living state. Under symbiosis, however, distinctive features, such as a single swollen bacteroid in one symbiosome, relatively narrow symbiosome space, and polyploid cells were observed. The morphotype of the PnptII-parA bacteroid is reminiscent of terminal differentiation in some IRLC indeterminate nodules, but S. rostrata is not thought to produce the NCR peptides that induce terminal differentiation in rhizobia. In addition, the transcript patterns of many symbiosis-related genes elicited by PnptII-parA were different from those elicited by the wild type. Accordingly, we propose that the particular symbiosome formation in PnptII-parA stem-nodules is due to cell cycle disruption caused by excess ParA protein in the symbiotic cells during nodulation.